Effect of Rhizobium Symbiosis on Low-Temperature Tolerance and Antioxidant Response in Alfalfa (Medicago sativa L.) - Liu, Yu-Shi; Geng, Jin-Cai; Sha, Xu-Yang; Zhao, Yi-Xin; Hu, Tian-Ming; Yang, Pei-Zhi (Frontiers in Plant Science, 2019)
Low temperature-induced stress is a major environmental factor limiting the growth and development of plants. Alfalfa (Medicago sativa L.) is a legume well known for its tolerance of extreme environments. In this study, we sought to experimentally investigate the role of rhizobium symbiosis in alfalfa’s performance under a low-temperature stress condition. To do this, alfalfa ‘Ladak+’ plants carrying active nodules (AN), inactive nodules (IN), or no nodules (NN) were exposed to an imposed low temperature stress and their survivorship calculated. The antioxidant defense responses, the accumulation of osmotic regulation substances, the cell membrane damage, and the expression of low temperature stress-related genes were determined in both the roots and the shoots of alfalfa plants. We found that more plants with AN survived than those with IN or NN under the same low temperature-stress condition. Greater activity of oxidation protective enzymes was observed in the AN and IN groups, conferring higher tolerance to low temperature in these plants. In addition, rhizobia nodulation also enhanced alfalfa’s ability to tolerate low temperature by altering the expression of regulatory and metabolism-associated genes, which resulted in the accumulation of soluble proteins and sugars in the nodulated plants. Taken together, the findings of this study indicate that rhizobium inoculation offers a practical way to promote the persistence and growth potential of alfalfa ‘Ladak+’ in cold areas.